2019
DOI: 10.1038/s41598-019-48748-3
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of safety, biodistribution and pharmacokinetics of laser-synthesized gold nanoparticles

Abstract: Capable of generating plasmonic and other effects, gold nanostructures can offer a variety of diagnostic and therapy functionalities for biomedical applications, but conventional chemically-synthesized Au nanomaterials cannot always match stringent requirements for toxicity levels and surface conditioning. Laser-synthesized Au nanoparticles (AuNP) present a viable alternative to chemical counterparts and can offer exceptional purity (no trace of contaminants) and unusual surface chemistry making possible direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(147 citation statements)
references
References 74 publications
(84 reference statements)
8
136
0
3
Order By: Relevance
“…The change of bimodal NP size distribution due to adding a solvent into the water media can be explained in terms of diffusion process, which is Additionally, the experimental measurements show that one can achieve the generation of a single distribution only. This is possible either by means of changing the irradiation parameters [14,30] or by means of adding different solvents [12,20,28,29]. While the effect of the irradiation parameters were accounted for in both theories of two distributions generation suggested above due to the same MD-TTM approach used [39], both Molecular Dynamics models used for water [43,50] did not include any chemistry since the possibility for the electron density changes, which can lead to the establishment of new type of bonding (chemical reactions, dissociation), was not considered explicitly due to its extremely high computational cost.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of bimodal NP size distribution due to adding a solvent into the water media can be explained in terms of diffusion process, which is Additionally, the experimental measurements show that one can achieve the generation of a single distribution only. This is possible either by means of changing the irradiation parameters [14,30] or by means of adding different solvents [12,20,28,29]. While the effect of the irradiation parameters were accounted for in both theories of two distributions generation suggested above due to the same MD-TTM approach used [39], both Molecular Dynamics models used for water [43,50] did not include any chemistry since the possibility for the electron density changes, which can lead to the establishment of new type of bonding (chemical reactions, dissociation), was not considered explicitly due to its extremely high computational cost.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…In the absence of ligands, the colloidal NPs are stable [16] and have bare (ligand-free) surface, which opens up prospects for a variety of applications in energy [21], catalysis [22] and healthcare [23,24]. As an example, we recently showed that bare Au-based NPs can provide one order of magnitude better electrocatalytic activity toward glucose oxidation compared to all chemically synthesized counterparts [25], prominent response SERS-based bioidentification tasks [26,27], as well as a much-reduced toxicity in biomedical applications [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…GNPs coupled with various molecules have been investigated extensively as a multifunctional platform for cellular imaging [4], biosensing [5] and targeted drug delivery in tumour immunotherapy and photothermal therapy [6][7][8]. Due to the chemically inert nature of Au, GNPs are expected to be biocompatible, as we demonstrated previously [9], along with several other groups [10][11][12][13]. In contrast, some publications addressed their adverse effects [14][15][16][17], which has raised concern about their impact on human health.…”
Section: Introductionmentioning
confidence: 89%
“…Regarding the biodistribution, a recent work demonstrated a rapid elimination of colloidal AuNPs from blood circulation in a rats model, and liver and spleen accumulation without inducing adverse effects or inflammation [59]. Au comprised in passion fruit-like nanoarchitectures (NAs) were studied in murine models demonstrating the excretion by renal and biliary pathways without nephrotoxicity up to 150 mg kg −1 [60].…”
Section: Aunpsmentioning
confidence: 99%